Superior hypertension control with betablockade in the European Sleep Apnea Database. (25th November 2020) - Svedmyr, S; Hedner, J; Zou, D; Parati, G; Ryan, S; Hein, H; Pepin, J.L; Tkacova, R; Marrone, O; Schiza, S; Basoglu, O.K; Grote, L
Abstract: Background: Arterial hypertension is highly prevalent and frequently difficult to control in patients with obstructive sleep apnea (OSA). High sympathetic activity is a hallmark physiological phenomenon in OSA. We hypothesized that antihypertensive drugs with sympathetic inhibitory properties, in particular beta blockers (BB), may be particularly efficacious in OSA patients. Methods: Hypertensive OSA patients receiving blood pressure lowing treatment in the European Sleep Apnea Database (ESADA) were analyzed (n=5818, 69% men, age 58±11 years, body mass index 33±7 kg/m 2, apnea hypopnea index 34±26 events/h). Antihypertensive medications (BB, diuretic, renin-angiotensin blocker [RAB], calcium channel blocker [CCB], and centrally acting antihypertensive [CAH]) were classified according to ATC code. Office blood pressure was compared in patients with mono- or combination therapy controlling for confounders. Results: Poorly controlled systolic blood pressure according to the ESC/ESH guidelines was found in 66% of patients. Patients receiving monotherapy with RAB, CCB or CAH had 2.2 [95% CI, 1.4–3.0], 3.0 [1.9–4.1] and 3.0 [1.7–4.7] mmHg higher systolic blood pressure compared with those on BB (adjusted model, p=0.007, 0.008 and 0.017, respectively). In those with a combination of two antihypertensive drugs, systolic blood pressure was 3.3 [2.4–4.3], 2.2 [1.3–4.3] and 2.3 [1.4–3.3] mmHg higher in those on CCB/RAB, diuretic/RAB or BB/RAB compared with those on BB/diuretic (adjusted model, p<0.001, 0.019 and 0.001, respectively). Conclusions: Uncontrolled blood pressure was common in OSA patients with antihypertensive medication. Patients treated with BB alone or in combination with diuretic was associated with a lower systolic pressure in this large clinical cohort. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): European Respiratory Society funded Clinical Research Collaboration (2015-2020)